2015
DOI: 10.2516/ogst/2015018
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Value Assessment of Oil and Gas Firms to Ambidexterity Theory Using a Mixture of Normal Distributions

Abstract: -Oil and gas exploration and production firms have return profiles that are not easily explained by current financial theory -the variation in their market returns is non-Gaussian. In this paper, the nature and underlying reason for these significant deviations from expected behavior are considered. Understanding these differences in financial market behavior is important for a wide range of reasons, including: assessing investments, investor relations, decisions to raise capital, assessment of firm and manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…They considered supply and demand uncertain and investigated their effects on the design of the supply chain. Casault et al [14] studied North American oil and gas exploration and production firms. They showed that these firms have rapid and large fluctuation in stock value.…”
Section: Introductionmentioning
confidence: 99%
“…They considered supply and demand uncertain and investigated their effects on the design of the supply chain. Casault et al [14] studied North American oil and gas exploration and production firms. They showed that these firms have rapid and large fluctuation in stock value.…”
Section: Introductionmentioning
confidence: 99%